Melodias da infância: a musicalização na Educação Infantil - Faustino, Caroline Mayoral (Universidade Federal de São Carlos, 2024)
Musicalization in Early Childhood Education is a field of research and pedagogical practice that has significant relevance in the learning of young children in daycare. In Early Childhood Education, the responsibility for working pedagogically with music generally falls on teachers specialized in Early Childhood Education, who have a degree in Pedagogy and not in Music. In this sense, the present study takes as a problem question: “How has musicalization been carried out in Early Childhood Education according to publications in the area?” To answer this main question, a bibliographical research was carried out to find out what educational legislation is aimed at teaching music in Early Childhood Education; what the child learns in musicalization, and what the experiences of musical education in daycare centers have been like. As a result, it was found that the relationship with music must be provided to children from an early age; that children's musical education actions become more meaningful through playing; that musical experiences in daycare centers favor the construction of an affective environment for learning, integration and strengthening bonds; and that there is a great need for musical education in Pedagogy Degree courses, so that future Pedagogues develop an interest in the area and feel confident in seeking musical knowledge; plan educational activities with music for young children, and build more musical spaces in the daycare center with the children.
Childhood melodies: musicalization in Early Childhood Education
Keywords: Musicalização; Musicalization; Educação Infantil; Early Childhood Education; Pedagogia; Pedagogy; Formação Docente; Teacher Education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO